"Disgusting Details Which Are Best Forgotten": Disclosures of Child Sexual Abuse in Twentieth-Century Britain. (3rd January 2018) - Delap, Lucy
Abstract: For those who by the end of the twentieth century came to be termed "survivors" of child sexual abuse, different genres and forms have been available to narrate and evaluate that abuse. This article explores the reception and practical results of such disclosures: the unpredictable effects of telling, and the strategies of containment, silencing, or disbelief that greeted disclosures. I make note of the ethical challenges of writing the history of child sexual abuse and conclude that twenty-first-century observers have been too ready to perceive much of the previous century as a period of profound silence in relation to child sexual abuse. At the same time, historical and sociological accounts have also been too ready to claim the final third of the twentieth century as a period of compulsive disclosure and fluency in constructing sexual selves. The history of child sexual abuse reveals significant barriers to disclosure in the 1970s and 1980s, despite new visibility of child sexual abuse in the media and through feminist sexual politics. Attention to such obstacles suggests the need to rethink narratives of "permissive" sexual change to acknowledge more fully the ongoing inequities and hierarchies in sexual candor and voice.